A person living in actual co-habitation in the doctrine and judicature in substantive and procedural penal law - Kubica, Marta (The Opole Studies in Administration and Law, 2017)
The Penal Code presently in force provides for a “person living in actual co-habitation” and it stipulates in Article 115 § 11 the definition of “the person next of kin”. According to the invoked provision “the person next of kin shall be a spouse, ascendant, descendant, brother or sister, a relative in the same line or degree, a person being an adopted relation as well as his spouse, and also a person living in actual co-habitation.” Numerous differences and doubts arise in the doctrine and judicature when one attempts to decode the term “a person living in actual co-habitation” as it has not been strictly defined by the legislator. The results of its interpretation by way of linguistic, systematic and functional directives lead to the conclusion that the term contained in Article 115 § 11 of the Penal Code “a person living in actual co-habitation” indicates a person living with another person in such a factual relationship, where there are between them simultaneously spiritual, physical and economic bonds. It is possible to establish the existence of a relation of “living in actual co-habitation” also when the lack of one of such bonds is objectively justified. The difference of the sexes of persons living in such co-habitation is not a requisite condition to establish that they actually live in co-habitation within the meaning of Article 115 § 11 of the Penal Code.